A HYBRIDIZED CONTINUOUS/DISCONTINUOUS GALERKIN FORMULATION FOR STOKES PROBLEMWITH CONTINUOUS TRACE SPACE - P. Fernandes, Katia; Mansur, Webe João; G.D. do Carmo, Eduardo (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
In this paper is presented a new hybridized continuous / discontinuous Galerkin formulation via continuous trace space for the Stokes problem. The method possesses unique features which distinguish itself from other methods. One of these features is that all the discontinuous variables are eliminated at element level as function of continuous trace variable, reducing thus the number of degrees of freedom and consequently the global system. Continuity and weak coercivity are presented in a suitable norm for the proposed formulation. Error estimates are also well established for velocity and pressure. Numerical experiments with the problem having smooth solution confirm the error estimates as well as the robustness of the formulation presented in this paper. Also, the numerical experiments with the classical cavity problem showed that the method presented here possesses a good ability for capturing the singularities of the pressure on the corners.